Implementasi Pembelajaran Cake Decoration pada Siswa Berkebutuhan Khusus (Tunarungu) oleh Politeknik Pariwisata Makassar - Zaenal, Faisal Akbar; Anas, Muhammad; Mustamin, Hasmawati Mansyur; Septian, Hilman; Faina, Nur (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This community service project aims to implement cake decoration learning for deaf students at SLB.C YPPLB 2 Makassar. This program is a collaboration between the Makassar Tourism Polytechnic and SLB.C YPPLB 2 Makassar, aiming to provide vocational skills to students with special needs. The teaching methods used include visual, manual, cooperative, and total communication methods, with deductive, expository, and heuristic strategies. The training was conducted over two days, covering the introduction of tools and materials, basic piping bag techniques, making buttercream frosting, cake covering techniques with fondant, creating decorations, and cake decoration design. The training results showed an improvement in students' cake decoration skills, evident from the independent projects they produced. The tiered wedding cake they made demonstrated a good understanding of structure, decoration techniques, and creativity in design. This program not only enhanced the students' technical skills but also boosted their confidence. The implications of this program include career development potential in the culinary industry for deaf students and the importance of collaboration between higher education institutions and special needs schools in creating inclusive learning opportunities.